RARE-07. EFFICACY AND SAFETY OF LAROTRECTINIB IN PEDIATRIC PATIENTS WITH TROPOMYOSIN RECEPTOR KINASE (TRK) FUSION-POSITIVE PRIMARY CENTRAL NERVOUS SYSTEM (CNS) TUMORS. (1st June 2021) - Perreault, Sébastien; Doz, François; Geoerger, Birgit; Nysom, Karsten; Øra, Ingrid; Boni, Valentina; Chisholm, Julia; DuBois, Steven G; Gerber, Nicolas U; Goto, Hiroaki; Grilley-Olson, Juneko E; Hansford, Jordan R; et al.
Abstract: Background: NTRK gene fusions are oncogenic drivers in various CNS and non-CNS tumors. Larotrectinib is a highly selective TRK inhibitor approved to treat patients with TRK fusion cancer, with an objective response rate (ORR) of 78% across multiple non-CNS cancers (McDermott et al, ESMO 2020). We report updated data on pediatric patients with TRK fusion-positive primary CNS tumors. Methods: Patients aged <18 years with primary CNS tumors harboring an NTRK gene fusion enrolled in two clinical trials (NCT02637687, NCT02576431) were identified. Larotrectinib was administered until disease progression, withdrawal, or unacceptable toxicity. Response was investigator assessed. Results: By July 2020, 26 pediatric patients with TRK fusion-positive CNS tumors were treated. Tumor histologic subtypes included high-grade glioma (n=13), low-grade glioma (n=7), glioneuronal tumor (n=2), neuroepithelial tumor (n=2), CNS neuroblastoma (n=1), and small round blue cell tumor (n=1). Median age was 7.0 years (range 1.3–16.7). The ORR was 38% (95% CI 20–59%): 3 complete responses, 7 partial responses (including 2 pending confirmation), 14 stable disease, and 2 progressive disease. The ORR in patients with high-grade glioma was 38% (95% CI 14–68%). Nineteen of 21 patients (90%) with measurable disease had tumor shrinkage. The 24-week disease control rate was 77% (95% CI 56–91%). Median duration of response (DoR), PFS and overall survival (OS) were not reached. The 12-month rates for DoR, PFS and OS were 75%, 65%, and 86%, respectively. Duration of treatment ranged from 1.2 to 31.3+ months. Treatment-related adverse events were reported for 15 patients (58%) and were Grade 3–4 in 3 patients (12%), with no discontinuations related to larotrectinib. Conclusions: In pediatric patients with TRK fusion-positive CNS tumors, larotrectinib demonstrated durable responses, high disease control rate, and good tolerability. These results support testing for NTRK gene fusions in pediatric patients with CNS tumors.